2014
DOI: 10.1016/j.geomorph.2014.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of multiresolution segmentation for delimiting drumlins in digital elevation models

Abstract: Mapping or “delimiting” landforms is one of geomorphology's primary tools. Computer-based techniques such as land-surface segmentation allow the emulation of the process of manual landform delineation. Land-surface segmentation exhaustively subdivides a digital elevation model (DEM) into morphometrically-homogeneous irregularly-shaped regions, called terrain segments. Terrain segments can be created from various land-surface parameters (LSP) at multiple scales, and may therefore potentially correspond to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 48 publications
(94 reference statements)
0
64
0
4
Order By: Relevance
“…Several publications treat the aspect of assessing the accuracy of landform mapping approaches with more than one method in order to derive a more comprehensive estimation on the overall quality of the classification results [14,17,29,39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several publications treat the aspect of assessing the accuracy of landform mapping approaches with more than one method in order to derive a more comprehensive estimation on the overall quality of the classification results [14,17,29,39].…”
Section: Discussionmentioning
confidence: 99%
“…Schmidt and Andrew [6] presented an approach applied at various scales of curvature. Eisank et al [17] recently presented an approach to assess the outcomes of multiresolution segmentation for delimiting drumlins from digital elevation models. However, landform mapping may also be carried out only on satellite images or other 2D information.…”
Section: Landform Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…, on the other hand, are designed terrains within which key components are known a priori, and so they have facilitated some progress on these and related questions. Specifically, synthetic DEMs were used to determine an optimal semi-automated method for drumlin extraction and to assess multi-resolution segmentation algorithms for delimiting drumlins (Eisank, Smith, & Hillier, 2014). In addition, a pilot study on manual mapping tentatively indicated that drumlin amplitude may be the key dimension governing drumlin detectability (Figure 1(c)) (Arumgam et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Step A. Following successful applications of multiresolution segmentation (MRS) in mountainous environments (AguirreGutierrez et al, 2012;Anders et al, 2013;Eisank et al, 2014) an iterative algorithm was developed producing 125 parameter combinations, similarly to the work of Clinton et al (2010). The parameter settings used for scale parameter are 10, 20, 30, 40 and 50, for the shape parameter 0.1, 0.3, 0.5, 0.7, 0.9 and for compactness 0.1, 0.3, 0.5, 0.7 and 0.9.…”
Section: Land Cover Change Detectionmentioning
confidence: 99%